Prototype of an internet of things based durian tree smart switch water and soil monitoring system / Nur Syahirah Mohamed Zaki ... [et al.] - Mohamed Zaki, Nur Syahirah; Mohd Ramli, Mohd Hanif; Mohamed, Zulkifli; Khusaini, Nurul Syuhadah (Smart Manufacturing Research Institute (SMRI), 2025)
This paper presents an IoT-based monitoring system designed to address the challenges durian farmers face when managing remote orchards. The prototype integrates soil nutrient sensors that measure critical parameters (pH, NPK, humidity, temperature) with water level monitoring and automated irrigation control. Using ESP32 microcontrollers, modbus protocols, and solar power, the researchers created a sustainable system that transmits real-time data to a Node-RED dashboard via MQTT, storing historical information in MySQL databases. The system was validated through comparative testing against laboratory soil analysis, achieving acceptable error margins (6.25% for pH, 13.33% for Nitrogen). The smart water management component successfully automated irrigation based on predetermined thresholds, with both automatic and manual control options available through the user-friendly interface. Beyond the technical implementation, cost analysis revealed significant economic advantages compared to traditional monitoring methods, with one-time installation costs of approximately RM700 plus minimal annual subscription fees replacing monthly labor expenses of RM700-1500. This system represents a practical advancement in precision agriculture for durian cultivation, enabling farmers to make informed decisions about fertilization and irrigation while reducing the burden of managing remote orchards.